Dual 3-phase bridge multilevel inverters for AC drives with voltage sag ride-through capability - Fernao Pires, Vitor (2019)
One of the main power quality issues that can affect variable speed drives (VSDs) is the occurrence of voltage sags on their AC power supply. Voltage sags can affect the inverter nominal operation, leading to a malfunction of the AC motor. This paper presents an inverter with resilient capability to voltage sags. The topology consists of two conventional three-phase bridge inverters arranged to require just a single DC source. This inverter is also characterized by a voltage multilevel operation, providing the full advantages of multilevel converters without the need for level balancing. Associated with this AC motor driver, a control system based on a field-oriented controller with a vector voltage modulator that will enable voltage sag ride-through capability is proposed. The proposed control system does not require any changes in the occurrence of voltage sags. To verify the characteristics of the proposed drive and control system, simulation tests are provided. Simulation results confirm the voltage sag resilient capability of the proposed multilevel converter.